The Relevance of Witness Literature to the Concept of Human Rights - Baltrimienė, Milda (Problemos, 2024)
The paper analyses whether witness literature could supplement the existing discussion on the nature of human rights. Contemporary theories of human rights are divided into two main groups – ethical and political theories. The latter theories present different conception of human dignity which is the fundamental concept for the understanding of human rights. The author claims that witness literature, by virtue of its frequent focus on the issues of human dignity, can assist in evaluating the arguments presented by ethical and political theories, thus contributing to the ongoing discussion and to the better understanding of human rights.
Keywords: human rights; political theories; ethical theories; dignity; witness literature